2013
DOI: 10.1371/journal.pone.0054013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Placental Telomere Length during Pregnancies Complicated by Intrauterine Growth Restriction

Abstract: ObjectivesRecent studies have shown that telomere length was significantly reduced in placentas collected at delivery from pregnancies complicated by intrauterine growth restriction secondary to placental insufficiency. Placental telomere length measurement during ongoing pregnancies complicated by intrauterine growth restriction has never been reported. This was the main objective of our study.MethodsIn our center, late chorionic villus samplings were performed between 18 and 37 weeks of amenorrhea in 24 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…2527 Shorter placental TL has been associated with racially disparate pregnancy complications such as FGR, GDM, and preeclampsia. 5,8,2832 Correlations between placental TL and gestational age, socioeconomic status, and parity have also been reported. 30,33,34 To date no previous studies have addressed racial differences in placental TL.…”
Section: Introductionmentioning
confidence: 91%
“…2527 Shorter placental TL has been associated with racially disparate pregnancy complications such as FGR, GDM, and preeclampsia. 5,8,2832 Correlations between placental TL and gestational age, socioeconomic status, and parity have also been reported. 30,33,34 To date no previous studies have addressed racial differences in placental TL.…”
Section: Introductionmentioning
confidence: 91%
“…To date, no study investigated the relationships between placental telomere length and risk of PA. Investigators have previously made consistent observations of shortened placental telomeres in pregnancies complicated by preeclampsia as well as severe intra-uterine growth restriction (IUGR) secondary to placental insufficiency (11, 22, 23). Other investigators have also shown a decrease in telomerase activity during placental maturation leading to suggestions that dysfunctional telomeres might be part of the mechanisms of placental aging during pregnancy (24, 25).…”
Section: Discussionmentioning
confidence: 84%
“…Findings from a large Mendelian randomization study support a causal role of telomere length variation in age-related diseases (9). Investigators have also implicated shortened placental and leukocyte telomeres in the pathogenesis of pregnancy complications including preeclampsia, intrauterine growth retardation and gestational diabetes (10, 11). However, to our knowledge, telomere length shortening, particularly placental telomere length shortening, which can chronicle antepartum stress from oxidative stress, has not been investigated in relation to risk of PA.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length in placental mesenchymal core cells was estimated with a Q-FISH technique using PNA fluorescent telomere probes, as described previously [8,18,19,20]. Briefly, the slides were successively immersed in solutions of Tris-buffered saline, 3.7% formaldehyde, and then in the Dako™ pretreatment of the Telomere PNA FISH Kit (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…In many physiopathological conditions, such as hypoxia or oxidative stress, a shortening of telomere length has been described [4,5,7]. For example, our team recently reported reduced telomere length in placental mesenchymal core cells during pregnancies complicated by intrauterine growth restriction (IUGR) secondary to placental insufficiency [8]. …”
Section: Introductionmentioning
confidence: 99%